Employee Training and Firm Performance: Evidence from ESF Grant Applications - Pedro S. Martins (Institute of Labor Economics (IZA), 2021)
As work changes more quickly, firm-provided training may become more relevant. However, there is little causal evidence about the effects of training on firms. This paper studies a large training grants programme in Portugal, supported by the European Social Fund, contrasting firms that received the grants and firms that also applied but were unsuccessful. Combining several rich data sets, we compare a large number of potential outcomes of these firms, while following them over several years both before and after the grant decision. Our difference-in-differences models estimate significant positive effects on take up (training hours and expenditure), with limited deadweight; and that such additional training led to increased sales, value added, employment, productivity, and exports. These effects tend to be of at least 5% and, in some cases, 10% or more, and are robust in multiple dimensions.
Keywords: J24; H43; M53; 330; training subsidies; productivity; programme evaluation